Admission criteria and student success in a medical radiation sciences program. - Kwan J; Childs RA; Cherryman F; Palmer C; Catton P (Journal of Allied Health)
Determining admission criteria that will predict successful student outcomes is a challenging undertaking for newly established health professional programs. This study examined data from the students who entered a medical radiation sciences program in September 2002. By analyzing the correlation between undergraduate GPA, grades in undergraduate science courses, performance in program coursework, and post-graduation certification examination results, the authors determined admission criteria that were linked to successful student outcomes for radiological technology and radiation therapy students.